2020
DOI: 10.1515/ntrev-2020-0102
|View full text |Cite
|
Sign up to set email alerts
|

Advances in layered double hydroxide-based ternary nanocomposites for photocatalysis of contaminants in water

Abstract: Recently, photocatalysis technology has been widely considered as an effective method for solving environmental pollution issues and addressing the energy crisis. Hybrids of layered double hydroxide (LDH) exhibit excellent photocatalytic properties for use in the field of wastewater treatment due to the large interlayer spaces, chemical stability, and low cost. However, pristine LDH suffers from numerous limitations, such as insufficient visible light utilization and a high recombination rate of electron–hole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 126 publications
0
5
0
1
Order By: Relevance
“…In fact, with the exception of the 1 mmol/L batch, the charge equivalents of metal cations removed are higher than those related to exchangeable Ca 2+ , Na + , and K + in the TRM (Table S2). Therefore, inner- and outer-sphere bonding may occur either with the exposed oxygens of tobermorite and the hydroxyls forming the amorphous phase. , This hypothesis is confirmed by considering the small increase (between 0.1 and 0.3) of pH observed at the end of each treatment and attributed to zeolitic Ca 2+ , Na + , and K + cations released by tobermorite (metal cations, in view of the partial deprotonation of their aqua complexes, are more acidic). The adsorption rate of the 100 and 50 mmol/L solutions is very close (only a little faster) to that observed for the other concentrations.…”
Section: Discussionmentioning
confidence: 71%
“…In fact, with the exception of the 1 mmol/L batch, the charge equivalents of metal cations removed are higher than those related to exchangeable Ca 2+ , Na + , and K + in the TRM (Table S2). Therefore, inner- and outer-sphere bonding may occur either with the exposed oxygens of tobermorite and the hydroxyls forming the amorphous phase. , This hypothesis is confirmed by considering the small increase (between 0.1 and 0.3) of pH observed at the end of each treatment and attributed to zeolitic Ca 2+ , Na + , and K + cations released by tobermorite (metal cations, in view of the partial deprotonation of their aqua complexes, are more acidic). The adsorption rate of the 100 and 50 mmol/L solutions is very close (only a little faster) to that observed for the other concentrations.…”
Section: Discussionmentioning
confidence: 71%
“…The doping of metal cations in sheets can enhance the photocatalyst's properties by introducing charge defects and promoting charge separation [25,29]. The LDH-based ternary composites reviewed by Sun et al all exhibited excellent photocatalytic performance, which was attributed to the enhanced electron-hole separation efficiency due to doping with metals [30]. Second, the anion located in the interlayer gallery can be exchanged as long as the anion does not dissolve the metal ions from the host layers [31].…”
Section: Introductionmentioning
confidence: 99%
“…17–19 Ever since Garcia et al reported that a series of Zn-containing LDHs exhibit photocatalytic activity for oxygen-generation, 20 the application of LDHs in photocatalysis has attracted more and more research interest. 21–27 Among all the already investigated LDH-based photocatalysts, Ti-containing LDHs are extremely appealing. The presence of well-dispersed TiO 6 octahedra, with their electronic structure being capable of modification by the neighboring divalent MO 6 via covalent interactions, increases the mobility of the photogenerated charge carriers, while an intrinsic layered structure of LDHs facilitates the charge transformation on the surface to take part in redox reactions.…”
Section: Introductionmentioning
confidence: 99%